New Zealand’s School Dental Service over the Decades: Its Response to Social, Political, and Economic Influences, and the Effect on Oral Health Inequalities - Moffat, Susan M.; Foster Page, Lyndie A.; Thomson, W. Murray (Frontiers in Public Health, 2017)
New Zealand’s School Dental Service (SDS) was founded in 1921, partly as a response to the “appalling” state of children’s teeth, but also at a time when social policy became centered on children’s health and welfare. Referring to the Commission on Social Determinants of Health (CSDH) conceptual framework, this review reflects upon how SDS policy evolved in response to contemporary constraints, challenges, and opportunities and, in turn, affected oral health. Although the SDS played a crucial role in improving oral health for New Zealanders overall and, in particular, children, challenges in addressing oral health inequalities remain to this day. Supported by New Zealand’s Welfare State policies, the SDS expanded over several decades. Economic depression, war, and the “baby boom” affected its growth to some extent but, by 1976, all primary-aged children and most preschoolers were under its care. Despite SDS care, and the introduction of water fluoridation in the 1950s, oral health surveys in the 1970s observed that New Zealand children had heavily-filled teeth, and that adults lost their teeth early. Changes to SDS preventive and restorative practices reduced the average number of fillings per child by the early 1980s, but statistics then revealed substantial inequalities in child oral health, with Ma¯ ori and Pacific Island children faring worse than other children. In the 1990s, New Zealand underwent a series of major structural “reforms,” including changes to the health system and a degree of withdrawal of the Welfare State. As a result, children’s oral health deteriorated and inequalities not only persisted but also widened. By the beginning of the new millennium, reviews of the SDS noted that, as well as worsening oral health, equipment and facilities were run-down and the workforce was aging. In 2006, the New Zealand Government invested in a “reorientation” of the SDS to a Community Oral Health Service (COHS), focusing on prevention. Ten years on, initial evaluations of the COHS appear to be mostly positive, but oral health inequalities persevere. Innovative strategies at COHS level may improve oral health but inequalities will only be overcome by the implementation of policies that address the wider social determinants of health.